Antimicrobial use and resistance in food‐producing animals—How can we protect the efficacy of antibiotics for reproductive diseases?. (13th June 2022) - Magnusson, Ulf
Abstract: The ongoing emergence of antibiotic resistance jeopardizes efficacy of antibiotics in curing animals from bacterial infections that threaten their health, welfare and productivity. This review gives an overview of antimicrobial use data in food‐producing animals, a discussion on how antimicrobials are used for some infections in the reproductive system in cattle, the horse and pig in Europe where there are differences in treatment practices including options to refine the use of antibiotics, and finally, a presentation of the antibiotic resistance for some bacteria collected from the reproductive system. It is shown that there are differences in applied treatment regimens for, as well as prevention of, several reproductive diseases in Europe. Some of the treatments are not evidence‐based, which should be considered by clinicians and other stakeholders. It is concluded that a more refined and restrictive use of antibiotics could be achieved by adhering to evidence‐based guidelines by national and international expertise including the scientific literature when available. This may call for a re‐think among the animal health stakeholders regarding the use of antibiotics and may demand new skill‐sets in the animal health sphere.